Analysis Of Road Conditions Using The Method SDI (Surface Distress Index) On The Road Section Kesehatan Majalengka - Muhammad Farras Raihan Ramdhani; Ade Jaya Saputra (Fakultas Teknik Sipil dan Perencanaan, 2024)
Roads are a transportation infrastructure for the daily needs of human life in the world, roads are also one of the most important parts that help human activities, roads are composed of several hard materials which are doused with asphalt (liquid) solution so that the roads we use feel comfortable when driving. Damage to the road that occurs causes huge losses for its users, so road damage is also the main trigger for traffic jams on the road, resulting in a decrease in the functional and structural quality of the road. The research location is located on Jalan Kesehatan, Majalengka, the main access to the entrance to the Majalengka Hospital, is damaged so that traffic jams often occur at the location, which is the main trigger for road damage in the field. This research was carried out by surveying directly to the field and using the SDI (Surface Distress Index) method to help collect data in the field, and inventory in GIS (Geographic Information System). The researcher also concluded that in the research location, there were roads that were damaged, and maintenance had to be carried out immediately regularly, bearing in mind that this road is the main access for people who want to go to the Majalengka Hospital, the researcher also suggested that the road be widened, to minimize congestion and expedite the speed of transportation in research sites.